Light-responsive shape memory polymer composites - Wang, Yanmei; Wang, Yanen; Wei, Qinghua; Zhang, Juan (European polymer journal, 2022)
[Display omitted] Shape memory polymer composites (SMPC) are a kind of intelligent material that can change state from temporary situation to original form under the external stimulus. Among all actuating approaches, light-driven SMPC are particularly outstanding due to their features of easy operation and tele-control at a specified location. Consequently, this review will focus on the state-of-art light-responsive shape memory polymer composites. It covers the classification based on different wavelengths of driving light and illustrates the working principle of each photosensitive shape memory material with examples. Whereafter, listing the commonly used preparing methods of polymer composites and the technology for forming intelligent structures. Finally, the current applied research is shown and envisages future research directions.